Fate of field-applied labelled fertilizer nitrate on sandy soils - Yusop, Mohd Khanif; Cleemput, O. Van; Baert, L. (Springer, 1983)
A field study to determine the recovery and balance of N-15 labelled fertilizer N was conducted on barley (Hordeum vulgare L.) and on maize (Zea mays L.) in the sandy area of Belgium. The barley was fertilized with 60 kg N/ha with KNO3 enriched with 2.057 At. % N-15 excess, while the maize received 65 kg N/ha KNO3 labelled with 4.877 At.% N-15 excess. The amount of fertilizer N recovered in the harvested plant part was 79% and 84%, while the amount remaining in the soil was 12% and 11% in the barley and maize plot, respectively. The high yield and high fertilizer N recovery was attributed to low rainfall and N application as side dressing. Statistical analyses showed that the results obtained from the N-15 plot can be extrapolated to the whole field